Managing and Leading through African Philosophies at Secondary Schools in South Africa: A case study of King Cetshwayo District - Akorede Ayoola Asanre; Alan B. Buthelezi (AMAR (Andalas Management Review), 2026)
Participative management, grounded in ubuntu (humanness) and democratic principles, emphasises inclusive decision-making in organisational contexts. This study explores African management and leadership philosophies in secondary schools in post-apartheid South Africa, focusing on the King Cetshwayo District of KwaZulu-Natal. Adopting a quantitative research paradigm, data were collected through questionnaires from a sample of 180 secondary school principals. Findings from both empirical data and literature indicate that while participative management is conceptually acknowledged, its practical implementation remains uneven. The study highlights that African philosophies, particularly ubuntu and lekgotla (a participatory and consensus-driven approach to decision-making), provide a culturally relevant framework for enhancing school leadership and management. However, their effective integration requires deliberate efforts, including continuous professional development and supportive policy alignment. The study concludes that strengthening capacity-building initiatives for school leaders is essential for institutionalising participatory and context-responsive leadership practices in South African secondary schools.